Nuorten psykologinen oireilu, itsemyötätunto ja psykologinen joustavuus : sukupuolten väliset erot ja verkkopohjaisen HOT-intervention vaikuttavuus - Hintikainen, Jutta; Vainio, Eveliina (2024)
This thesis examined the psychological symptoms, psychological flexibility and self-compassion of adolescents as well as compared gender differences within these items. Additionally, the impact of Youth Compass Plus, a web-based acceptance and commitment therapy (ACT) intervention developed by University of Jyväskylä, was examined in regard to the variables of psychological symptoms, psychological flexibility and self-compassion. The thesis was executed as a part of project called Hyvä arki (Feeling good everyday) which aimed to support the well-being of adolescents in secondary school in a town in western Finland through a five-week ACT-intervention. The sample of the thesis was 120 and the study was conducted by using